2011
DOI: 10.4103/0974-7796.75862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on bladder function in patients with overactive bladder symptoms

Abstract: Objectives:To evaluate the effect of caffeine at the dose of 4.5 mg/kg on bladder function in overactive bladder (OAB) adults.Materials and Methods:Nine women and three men aged 21-40 years with OAB symptoms were included. Each subject drank 8 ml/kg of water with and without caffeine at two separate sessions. Cystometry and uroflowmetry were performed 30 minutes after each drink. The effects of caffeine on urodynamic parameters were compared.Results:After caffeine ingestion, the mean volume at bladder filling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 14 publications
3
45
0
3
Order By: Relevance
“…The fluid balance chart establishes patterns and type of fluid intake. The types of fluid taken is important especially those that may irritate the bladder such as caffeinated, carbonated or citrus drinks (Miller et al, 2016, Lohsiriwat., Hirunsai and Chaiyaprasithi, 2011and Maserejian et al, 2013 (Staskin et al 2009, NICE, 2015aand NICE, 2015b can help determine how the bladder dysfunction is affecting them individually.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid balance chart establishes patterns and type of fluid intake. The types of fluid taken is important especially those that may irritate the bladder such as caffeinated, carbonated or citrus drinks (Miller et al, 2016, Lohsiriwat., Hirunsai and Chaiyaprasithi, 2011and Maserejian et al, 2013 (Staskin et al 2009, NICE, 2015aand NICE, 2015b can help determine how the bladder dysfunction is affecting them individually.…”
Section: Assessmentmentioning
confidence: 99%
“…if it is too high or too low and caffeine restriction (Lohsiriwat, Hirunsai andChaiyaprasithi, 2011 andMaserejian et al, 2013).  Treatment of constipation  Advice to stop smoking  Advice about weight loss if their BMI is over 30 (Lucas et al 2015)  Bladder retraining including time delayed voiding.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Interestingly, BSM has all the enzymes required to convert ATP to adenosine, which is likely to be important because adenosine causes smooth muscle to relax. In this context, a number of studies have shown that caffeine can exacerbate lower urinary tract symptoms, including OAB (52)(53)(54). Although the mechanism remains unclear because caffeine has several cellular effects, it is known to inhibit adenosine receptors at the low doses found from drinking coffee and, thus, may inhibit detrusor relaxation (53).…”
Section: Detrusor Smooth Musclementioning
confidence: 99%
“…In this context, a number of studies have shown that caffeine can exacerbate lower urinary tract symptoms, including OAB (52)(53)(54). Although the mechanism remains unclear because caffeine has several cellular effects, it is known to inhibit adenosine receptors at the low doses found from drinking coffee and, thus, may inhibit detrusor relaxation (53). Intriguingly, purinergic signaling becomes more prominent in disease and in aging (55)(56)(57) and may emerge to play a dominant role in patients with partial outlet obstruction and interstitial cystitis, potentially accounting for up to 65% of the total contraction force (58).…”
Section: Detrusor Smooth Musclementioning
confidence: 99%
“…Regular caffeine consumers have been reported to exhibit symptoms of dependence (Striley et al 2011), and caffeine abstinence following habitual consumption has been associated with symptoms such as fatigue, difficulty concentrating and headaches (Juliano et al 2012). Caffeine is known to cause a mild diuresis (Riesenhuber et al 2006;Lohsiriwat et al 2011) which may result in increased urinary frequency and may also affect detrusor stability (Creighton and Stanton 1990). Higher caffeine intakes have been associated with urinary incontinence (UI) (Gleason et al 2013) and caffeine intake has been associated with OAB.…”
Section: Introductionmentioning
confidence: 99%